Incidence of chronic Hepatitis B among Orang Asli in Pahang - Mohd Firdaus, Mohd Al-Baqlish; Poh, Tee Hoi (IIUM Medical Journal Malaysia, 2016)
Introduction: The rate of Hepatitis B infection in Malaysia is 4.7% and the prevalence of Hepatitis B infection varies among ethnic group in Malaysia. The estimated prevalence of chronic Hepatitis B among Orang Asli in Malaysia is 8.3%. Methods: 232 Orang Asli participated in this study on a voluntary basis during two health screening in two Orang Asli Villages. Subjects serum HBsAg and HBsAb titres were taken and analyzed. Results: From 232 participants, there are 24 subjects who are HBsAg positive (10.3%) and only 15.9% of the population study has immunity to Hepatitis B. Conclusions: The incidence of chronic Hepatitis B among Orang Asli in Pahang is higher than the general population, and the rate of immunity to Hepatitis B are low compared to the general population.